Molecular cloning of the breakpoints of a complex Philadelphia chromosome translocation: identification of a repeated region on chromosome 17. - McKeithan, T W (1992)
Complex translocations in chronic myelogenous leukemia involve various chromosomes, in addition to chromosomes 9 and 22, in a nonrandom fashion. We have analyzed the DNA from leukemia cells characterized by a complex translocation, t(9;22;10;17)(q34;q11;p13;q21), by using the techniques of Southern blot hybridization, in situ hybridization, and molecular cloning; one of the breakpoints is at 17q21, a band that is frequently involved in complex 9;22 translocations. All of the breakpoint junctions and the corresponding normal sequences from the four involved chromosomes have been molecularly cloned. Restriction mapping is consistent with a simple concerted exchange of chromosomal material among the four chromosomes, except that additional changes appeared to have occurred within the chromosome 17 sequences. The cloned sequences on chromosome 17 at band q21 were found to be repeated in normal cells. By fluorescence in situ hybridization, a strong signal is seen at 17q21, but a weaker signal is also present at 17q23. By comparison with other primate species, an inversion in chromosome 17 during evolution appears to be responsible for the splitting of the cluster of repeat units in normal human cells.